Temporality and deconstruction as interrelated strategies in contemporary clothing design - Hasem, Amina (Art and Design, 2025)
The study was devoted to identifying the connections between temporality as an aesthetic category and deconstruction as a creative trend in contemporary clothing design. The article used a comprehensive approach that combined methods of cultural, visual-analytical and art analysis, which made it possible to study deconstruction and temporality not only as separate concepts, but also as interrelated strategies in clothing design and design in general. The use of these strategies and the analysis of their interconnection were justified, in particular, how the sense of time and its cyclicality is embodied in deconstructive forms, as well as methods of experimental clothing design. It has been determined that the combination of these approaches forms a unique concept of time, which is assembled in parts, corresponding to the contemporary postmodern worldview. Particular attention was focused on the manifestations of these strategies in contemporary design practices and their interpretation in Ukrainian and world fashion. Deconstruction has proven to be an effective tool for actualising time as a conceptual category. Typical techniques that combine temporal and deconstructive methods have been systematised. Using examples from the work of leading international and Ukrainian designers (Maison Margiela, Comme des Garcons, Junya Watanabe, DZHUS, Litkovska, Gunia, KSENIASCHNAIDER), the article showed how contemporary artists integrate temporal sensitivity into design, specifically through the deconstruction of traditional forms. In particular, the Ukrainian context reveals its own attempts to “work with memory.” It has been confirmed that deconstruction in clothing design not only destroys fashion standards but also creates a new aesthetic of time, where the past, present, and future coexist in a single visual system. The results of the study offer innovative approaches to creating meaningful authorial clothing collections, in particular through the use of deconstruction and temporality. The materials can be used in educational programmes, scientific works and practical design activities.